Penatalaksanaan Anestesi untuk Gabungan Tindakan Seksio Sesarea dan Kraniotomi Tumor Otak - Wullur, Caroline; Boesoirie, M. Adli; Bisri, Dewi Yulianti (https://snacc.org/wp-content/uploads/2019/fall/Intl-news3.html, 2015)
Angka kejadian tumor intrakranial pada masa kehamilan sangat jarang. Keluhan seperti mual, muntah, nyeri kepala dan gangguan penglihatan serupa dengan hiperemesis dan eklampsia. Sebagian besar pasien tidak memerlukan tindakan emergensi namun pada beberapa kasus, kraniotomi tumor otak dilakukan lebih awal atau bahkan bersamaan dengan seksio sesarea. Seorang wanita 40 tahun, G3P2A0 datang dengan penurunan kesadaran GCS 6 (E2M2V2). CT-scan menunjukkan adanya masa pada daerah temporoparietal kiri, curiga high grade glioma, disertai dengan pergeseran midline dan perdarahan intratumoral. Pemeriksaan obstetri menunjukkan usia kehamilan 32 minggu dengan gawat janin. Dengan pertimbangan resiko herniasi dan gawat janin, pasien menjalani operasi emergensi seksio sesarea diikuti dengan kraniotomi tumor otak. Operasi berlangsung selama 6 jam. Pada pasien hamil dengan tumor otak, waktu pembedahan bergantung pada jenis tumor, usia kehamilan dan kondisi janin. Keberhasilan anestesi bergantung pada pengetahuan menyeluruh mengenai fisiologi dan farmakologi wanita hamil yang disesuaikan dengan individu terkait untuk mengontrol tekanan intrakranial, dengan tujuan menjaga kesejahteraan ibu dan anak.Anaesthetic Management for Combined Emergency Cesarean Section and Craniotomy Tumor RemovalThe occurrence of primary intracranial tumors in pregnancy is an extremely rare event. Symptoms of brain tumor include nausea, vomitting, headache, visual disturbances and seizures which mimic symptoms of pregnancy-related hyperemesis or eclampsia. These central nervous system disorders seldom require immediate surgical attention during pregnancy. However in very few cases, craniotomy tumor removal is performed earlier or even simultaneous with fetal delivery. A 40-year-old woman at 32 weeks of gestation presented to the emergency room with decreased level of consciousness GCS 6 (E2M2V2). CT scan revealed a mass lesion over the left temporoparietal region, suggestive of a high grade glioma, with midline shift and intratumoral bleeding. Obstetric examination revealed a single live fetus of 32 weeks gestation in distress. In view of high risk of herniation and fetal distress, she underwent emergency cesaren section followed by craniotomy tumor removal. Both procedures were completed in 6 hours. In a parturient with brain tumor, the time of combined surgery of tumor removal and cesarean section is decided upon clinical symptoms, type of tumor, gestational age and fetal viability. A successful anaesthetic management requires a comprehensive knowledge of physiology and pharmacology, individually tailored to control intracranial pressure while ensuring the safety of both mother and fetus.